In vivo regulation of gene expression and T helper type 17 differentiation by RORγt inverse agonists. Issue 3 (3rd April 2015) - Skepner, Jill; Trocha, Mark; Ramesh, Radha; Qu, Xiaoyan A.; Schmidt, Darby; Baloglu, Erkan; Lobera, Mercedes; Davis, Scott; Nolan, Michael A.; Carlson, Thaddeus J.; Hill, Jonathan; Ghosh, Shomir; et al.
Summary The orphan nuclear receptor, retinoic acid receptor‐related orphan nuclear receptor γt (RORγt), is required for the development and pathogenic function of interleukin‐17A‐secreting CD4+ T helper type 17 (Th17) cells. Whereas small molecule RORγt antagonists impair Th17 cell development and attenuate autoimmune inflammation in vivo, the broader effects of these inhibitors on RORγt‐dependent gene expression in vivo has yet to be characterized. We show that the RORγt inverse agonist TMP778 acts potently and selectively to block mouse Th17 cell differentiation in vitro and to impair Th17 cell development in vivo upon immunization with the myelin antigen MOG35–55 plus complete Freund's adjuvant. Importantly, we show that TMP778 acts in vivo to repress the expression of more than 150 genes, most of which fall outside the canonical Th17 transcriptional signature and are linked to a variety of inflammatory pathologies in humans. Interestingly, more than 30 genes are related with SMAD3, a transcription factor involved in the Th17 cell differentiation. These results reveal novel disease‐associated genes regulated by RORγt during inflammation in vivo, and provide an early read on potential disease indications and safety concerns associated with pharmacological targeting of RORγt.